Gold nanoparticles supported on LnPO4 (Ln = La, Ce) nanorods and nanospheroids as high performance catalysts for CO oxidation. (January 2018) - Yu, Huanhuan; Dong, Feng; Guo, Jiuli; Zhu, Baolin; Huang, Weiping; Zhang, Shoumin
Graphical abstract: Highlights: The comparative study of one-dimensional hexagonal LnPO4 (Ln = La, Ce) nanorods and three-dimensional monoclinic LnPO4 nanospheroids supported gold catalysts for CO oxidation was first reported. The morphologies of LnPO4 (Ln = La, Ce) have a profound influence on the catalytic activity of Au/LnPO4 for CO oxidation. Au/LaPO4 -nanorods could completely convert CO to CO2 at ambient temperature. Au/LnPO4 catalysts still possessed high catalytic activity after high-temperature treatment. Au/LnPO4 catalysts showed good stability over 10 h on stream. Abstract: Hexagonal LnPO4 (Ln = La, Ce) nanorods and monoclinic LnPO4 (Ln = La, Ce) nanospheroids (NSPs) were synthesized by hydrothermal methods Au/LnPO4 catalysts were prepared by a modified deposition-precipitation method. The samples were characterized by N2 adsorption-desorption, ICP, XRD, TEM, EDX, XPS, and CO2 -TPD. The catalytic tests for CO oxidation demonstrated that morphologies of LnPO4 would influence the activity of Au/LnPO4 . 1.0% Au/LaPO4 -NRs catalyst exhibited best catalytic activity achieving complete CO conversion at 25 °C among Au/LnPO4 catalysts. The sintering resistance of gold nanoparticles in Au/LnPO4 upon calcination was enhanced due to the strong metal-support interaction. Au/LnPO4 also showed good stability for CO oxidation with no deactivation after continuous operation for 10 h. The possible mechanism of CO oxidation on Au/LnPO4 catalysts was also briefly described.